State and independent audit: similarities and differences - Koloshko, Natalia; Nikitenko, Olga (My University, 2019)
The reformation of the Ukrainian economy, the formation of new types of economic relations between economic entities and the processes of integration into the world economy led to the development of the financial system, which in general corresponds to the realities of the modern market economy, the state system, the goals of socially oriented economic development of the country.
Keywords: state audit; independent audit; financial system; державний аудит; незалежний аудит; фінансова система; кафедра ділової іноземної мови та міжнародної комунікації